Psychological treatment of sexual problems. Thematic analysis of guidelines and recommendations, based on a systematic literature review 2001–2010. Issue 1 (2nd January 2016) - Almås, Elsa
ABSTRACT: In order to explore the basis for evaluation of quality in psychological treatment of sexual problems, a literature search, confined to publications between 2001 and 2010, was conducted in 2012. Two hundred sixty one articles were found and ordered according to the subject and type of publication. Thematic analysis of 37 articles on guidelines and recommendations for treatment of sexual problems is presented. Guidelines and recommendations published in the period from 2001 up to and including 2010 provides an overview of the discussion among professionals in the first decade of the 21st century. Six themes are analysed: (1) definitions of male and female dysfunctions, (2) prevalence of sexual problems, (3) lack of randomized and controlled trials, (4) need for a bio-psycho-social approach, (5) the subjective perspective, and (6) recommendations. Excerpts from the material pertaining to discussions and/or reflections on these themes are presented and discussed. The main conclusions are (1) the definition of psychological treatment is imprecise and needs clarification, (2) not every therapist should work with sexual problems, (3) sexual problems cannot be regarded as "dysfunctions" in the traditional biomedical understanding, but must be understood in a bio-psycho-social perspective, (4) psychological treatment is recommended in spite of lack of evidence, (5) the literature reflects a more reserved belief in pharmacological treatment, (6) material that qualifies as scientific evidence includes more than randomized and controlled trials and (7) combination treatment is recommended.